2021
DOI: 10.1039/d1tc03092b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, phase purification and magnetic characterization of the (Cr1−x, Mnx)2AlC MAX-phase

Abstract: The Cr2AlC MAX phase is a promising parent compound to introduce magnetism to nano-laminated ternary carbides by doping with Mn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…The latter revealed ferromagnetic characteristics up to 230 K with potential toward spintronics or magnetocaloric applications. , Since then, in both thin-film and bulk synthesis approaches, many doping studies with manganese on the M -site have been reported. As parent phases, predominantly chromium-based (Cr 2 A C) phases with A = Al, , Ga, , and Ge , were studied. However, particularly bulk approaches have faced the problem of competing side phases leading to only small Mn amounts that can be incorporated into the MAX phase structure (e.g., (Cr 0.94 Mn 0.06 ) 2 AlC, (Cr 1– x Mn x ) 2 GeC; x ≤ 0.25).…”
Section: Introductionmentioning
confidence: 99%
“…The latter revealed ferromagnetic characteristics up to 230 K with potential toward spintronics or magnetocaloric applications. , Since then, in both thin-film and bulk synthesis approaches, many doping studies with manganese on the M -site have been reported. As parent phases, predominantly chromium-based (Cr 2 A C) phases with A = Al, , Ga, , and Ge , were studied. However, particularly bulk approaches have faced the problem of competing side phases leading to only small Mn amounts that can be incorporated into the MAX phase structure (e.g., (Cr 0.94 Mn 0.06 ) 2 AlC, (Cr 1– x Mn x ) 2 GeC; x ≤ 0.25).…”
Section: Introductionmentioning
confidence: 99%
“…[124] In 2021, Sobolev et al were able to increase the Mnamount even up to 16 at-% using the arc melting technique, however, the magnetic ordering is restricted to paramagnetism. [125] Other non-conventional bulk synthesis approaches were made by Siebert et al applying a sol-gel approach to synthesize manganese-doped Cr 2 GaC with a doping level up to 16 %. While not in the bulk, the authors found Mn-rich areas of the MAX phase that may be magnetically ordered.…”
Section: Later Transition Metals As M-elementsmentioning
confidence: 99%
“…In 2021, Sobolev et al . were able to increase the Mn‐amount even up to 16 at‐% using the arc melting technique, however, the magnetic ordering is restricted to paramagnetism [125] . Other non‐conventional bulk synthesis approaches were made by Siebert et al .…”
Section: Variation Of Mmentioning
confidence: 99%
“…Recently, a new group of MAX phases was discovered with ordered quaternary [105][106][107][108][109][110][111], which expands MAX phases and opens a new window for tuning the nature of MAX phases and developing new MXenes. For example, Caspi et al [106] showed by high-resolution neutron diffraction analysis that the (Cr 0.5 V 0.5 ) n+1 AlC n system showed a strong tendency for V and Cr atoms to be ordered, with V occupying only the intermediate layer.…”
Section: Synthesis Of Mbenesmentioning
confidence: 99%